The Differential Growth Inhibition of Phytophthora spp. Caused by the Rare Sugar Tagatose Is Associated With Species-Specific Metabolic and Transcriptional Changes - Chahed, Abdessalem; Lazazzara, Valentina; Moretto, Marco; Nesler, Andrea; Corneo, Paola Elisa; Barka, Essaid Ait; Pertot, Ilaria; Puopolo, Gerardo; Perazzolli, Michele (Frontiers in Microbiology, 2021)
Tagatose is a rare sugar with no negative impacts on human health and selective inhibitory effects on plant-associated microorganisms. Tagatose inhibited mycelial growth and negatively affected mitochondrial processes in Phytophthora infestans, but not in P. cinnamomi. The aim of this study was to elucidate metabolic changes and transcriptional reprogramming activated by P. infestans and P. cinnamomi in response to tagatose, in order to clarify the differential inhibitory mechanisms of tagatose and the species-speciﬁc reactions to this rare sugar. Phytophthora infestans and P. cinnamomi activated distinct metabolic and transcriptional changes in response to the rare sugar. Tagatose negatively affected mycelial growth, sugar content and amino acid content in P. infestans with a severe transcriptional reprogramming that included the downregulation of genes involved in transport, sugar metabolism, signal transduction and growth-related process. Conversely, tagatose incubation upregulated genes related to transport, energy metabolism, sugar metabolism and oxidative stress in P. cinnamomi with no negative effects on mycelial growth, sugar content and amino acid content. Differential inhibitory effects of tagatose on Phytophthora spp. were associated with an attempted reaction of P. infestans, which was not sufficient to attenuate the negative impacts of the rare sugar and with an efficient response of P. cinnamomi with the reprogramming of multiple metabolic processes, such as genes related to glucose transport, pentose metabolism, tricarboxylic acid cycle, reactive oxygen species detoxification, mitochondrial and alternative respiration processes. Knowledge on the differential response of Phytophthora spp. to tagatose represent a step forward in the understanding functional roles of rare sugars.